Pelatihan Tilawah Untuk Meningkatkan Kecintaan Terhadap Al-Qur'an di TPQ Nurul Furqon An-Nuriyah Surabaya - M.Yusron Maulana El-Yunusi; M. Muhaimin (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
This study aims to evaluate the effectiveness of tilawah training in increasing students' love for the Qur'an at the Nurul Furqon An-Nuriyah Surabaya Al-Qur'an Education Park (TPQ). The method used is a qualitative approach with data collection through interviews, observations, and document analysis. The results of the study indicate that tilawah training carried out in a structured and systematic manner not only improves the ability to read the Qur'an, but also strengthens students' love and closeness to the Qur'an. Students showed increased interest and motivation in learning, and better understood the values ​​contained in the holy book. This study concludes that tilawah training is an effective strategy to build love for the Qur'an, and recommends the implementation of this program on an ongoing basis to achieve optimal results.